Emerging contaminants in Brazilian rivers: Occurrence and effects on gene expression in zebrafish (Danio rerio) embryos. (October 2018) - Sposito, Juliana C.V.; Montagner, Cassiana C.; Casado, Marta; Navarro-Martín, Laia; Jut Solórzano, Julio César; Piña, Benjamin; Grisolia, Alexeia B.
Abstract: Emerging contaminants (ECs) are synthetic or naturally occurring chemicals that are not commonly monitored despite having the potential of entering the environment and causing adverse ecological and/or human health effects. This study aimed to determine whether ECs are present in the surface waters of two rivers in Mato Grosso do Sul State, Brazil, and evaluate the effects of ECs mixtures at environmentally relevant concentrations on zebrafish ( Danio rerio ) gene expression. ECs concentrations were determined using solid-phase extraction and liquid chromatography-mass spectrometry. The ECs most frequently detected were caffeine, imidacloprid, 2-hydroxy atrazine, tebuthiuron, atrazine, and bisphenol A. We used these data to reconstruct ECs mixtures reflecting environmental concentrations, codenamed T1, T2, and T3. No effects were observed, so the concentrations were increased. After a preliminary evaluation of the No Observed Effect Concentration for each mixture, we analyzed changes in the expression of zebrafish target genes ( cyp1a, hsp70, cat, sod1, tsh, cyp19a1a, cyp19a1b, cyp26b1, casp8, sox2, cyb561d2, and thrb ). cat was overrepresented in T1 and underrepresented in the other treatments. All of the mixtures induced the expression of cyp19a1b, which is a marker for (xeno-)estrogen exposure, and two of them increased the expression of cyp1a, which is used to indicate the presence of dioxin-like compounds. The rivers studied had low EC concentrations, and there was no indication of any harmful effects on the zebrafish. However, intensive agricultural activity may result in unsuspected peaks of EC pollution, and subsequent negative effects on living organisms. Highlights: The occurrence of emerging contaminants (ECs) was investigated in rivers in the southern region of Mato Grosso do Sul, Brazil. We evaluated the potential toxicity of ECs mixtures on gene expression in zebrafish embryos. ECs mixtures at three different sampling sites induced the expression of cat, cyp19a1b, and cyp1a .